Identification of cell‐free DNA methylation patterns unique to the human left ventricle as a potential indicator of acute cellular rejection. Issue 6 (3rd April 2021) - Pattar, Sabrina; Aleinati, Mohammad; Iqbal, Fatima; Madhu, Aiswarya; Blais, Samuel; Wang, Xuemei; Dallaire, Frederic; Wang, Yinong; Isaac, Debra; Fine, Nowell; Greenway, Steven C.
Abstract: Increased levels of donor‐derived cell‐free DNA (dd‐cfDNA) in recipient plasma have been associated with rejection after transplantation. DNA sequence differences have been used to distinguish between donor and recipient, but epigenetic differences could also potentially identify dd‐cfDNA. This pilot study aimed to identify ventricle‐specific differentially methylated regions of DNA (DMRs) that could be detected in cfDNA. We identified 24 ventricle‐specific DMRs and chose two for further study, one on chromosome 9 and one on chromosome 12. The specificity of both DMRs for the left ventricle was confirmed using genomic DNA from multiple human tissues. Serial matched samples of myocardium ( n = 33) and plasma ( n = 24) were collected from stable adult heart transplant recipients undergoing routine endomyocardial biopsy for rejection surveillance. Plasma DMR levels increased with biopsy‐proven rejection grade for individual patients. Mean cellular apoptosis in biopsy samples increased significantly with rejection severity (2.4%, 4.4% and 10.0% for ACR 0R, 1R, and 2R, respectively) but did not show a consistent relationship with DMR levels. We identified multiple DNA methylation patterns unique to the human ventricle and conclude that epigenetic differences in cfDNA populations represent a promising alternative strategy for the non‐invasive detection of rejection.